Strawberry yields with high-tunnel and open-field cultivations and the relationship with vegetative and reproductive plant characteristics (2015)
In Colombia, high-tunnel systems may be a viable alternative for increasing the yields of strawberry crops due to their ability to prevent fruit losses and plant damage caused during periods of high precipitation. This study aimed to compare the yield and its relationship with vegetative and reproductive components of Albion and Monterey strawberry cultivars, established in open-field and high-tunnel systems in Cajica (Colombia), at 2,562 m a.s.l. and 4°56' N, 74°00' W. A combined analysis of the environments was carried out. A random complete block design was used in each environment with six replications for each cultivar. This study evaluated the relationship between the leaf area, the number of crowns, the number of leaflets, the number of flowers, the number of inflorescences, the number of flowers per inflorescence, the number of fruits, the incidence of foliar damage, the yield per plant and the fruit size. There were positive correlations between the vegetative variables and the reproductive variables, which explained why ‘Monterey’, a cultivar with more vigor, presented a higher yield that ‘Albion’. The growth conditions in the high-tunnel system promoted rapid vegetative growth in the ‘Monterey’ plants, with an increase in yield and a decrease in losses. The ‘Albion’ cultivar plants in the high-tunnel system presented a decrease in fruit losses; however, these plants did not present differences in the yield, as compared to the plants established in the open-filed system. Despite the benefits of a decrease in fruit losses due to rot seen in the high-tunnel system, this system had an increase in powdery mildew and calcium deficiency.